2021
DOI: 10.1186/s12889-021-11393-5
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic inequality in anaemia among men in India: a study based on cross-sectional data

Abstract: Background Undernutrition is a serious matter of public health concern in India. Existing studies, policies and programs focus on women and children thereby ignoring men in policymaking. This study examines the socio-economic inequality in anaemia levels among men in India and tries to decompose the factors behind it. Methods The fourth round of National Family Health Survey is used to fulfill the study objectives. The outcome variable of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Muslim men had greater risk of anaemia, which is similar to the findings from an earlier study [20]. This study also found that Christian men living in rural India were at significantly lower risk of anaemia, which was not highlighted previously by any scientific study and requires further investigation.…”
Section: Plos Global Public Healthsupporting
confidence: 90%
See 1 more Smart Citation
“…Muslim men had greater risk of anaemia, which is similar to the findings from an earlier study [20]. This study also found that Christian men living in rural India were at significantly lower risk of anaemia, which was not highlighted previously by any scientific study and requires further investigation.…”
Section: Plos Global Public Healthsupporting
confidence: 90%
“…A study in 2019 focused on the differentials of anaemia prevalence among men in India [19]. A recent study by attempted to decompose the factors that contribute to socioeconomic inequality in anaemia among men in India [20]. Also, Kumar et al assessed the correlates and geographic distribution of anaemia in men in the empowered action group (EAG) states of India [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the y-axis, the cumulative proportion of outcome variables (cognitive impairment) is plotted against the increasing percentage of the population ranked by the socioeconomic indicator (wealth index) on the x-axis to generate the concentration curve [ 38 ]. Such curves show whether or not socioeconomic inequality in the outcome variable (on the x-axis) prevails, with the index value being negative if the curve is above the line of equality (45-degree line), indicating that the outcome variable is disproportionally concentrated among the poor, and vice versa [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The range of C-index lies between − 1 to + 1. If the curve displays above the line of equality, the value of C-index is negative and indicates a disproportionally concentration of inequality among the poor [ 45 , 46 ]. If the curve falls below the line of equality, the value of C-index is positive, demonstrating a disproportionally concentrated inequality among the rich.…”
Section: Methodsmentioning
confidence: 99%